Interobserver Agreement of White Matter Tract Involvement in Gliomas with Diffusion Tensor Tractography - Abdel Razek, Ahmed Abdel Khalek; El-Serougy, Lamiaa; Ezzat, Amani; Eldawoody, Hany; El-Morsy, Ahmad (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Aim To assess with diffusion tensor tractography (DTT) the interobserver agreement of white matter tract involvement in patients with gliomas.Patient and Methods A prospective study was conducted on 35 patients (21 male, 14 female; age: 2–71 years) with gliomas that underwent DTT. Two independent readers assessed the patterns of involvement of the corticospinal tract, corpus callosum, optic radiation, and fasciculi as normal, edematous, displaced, infiltrated, or disrupted.Results Overall interobserver agreement of involvement of the white matter tracts was excellent (κ = 0.93; 95% confidence interval [CI], 0.91–0.95; p = 0.001). Interobserver agreement was excellent for involvement of corticospinal tracts (κ = 0.81; 95% CI, 0.57–1.00; p = 0.001), corpus callosum (κ = 0.91; 95% CI, 0.75–1.00; p = 0.001), optic radiation (κ = 0.77; 95% CI, 0.53–0.98; p = 0.001), and fasciculi (κ = 0.912; 95% CI, 0.81–0.99; p = 0.001. The interobserver agreement was excellent for tract edema (κ = 0.81; 95% CI, 0.57–1.00; p = 0.001), tract displacement (κ = 0.91; 95% CI, 0.75–1.00; p = 0.001), tract disruption (κ = 0.81; 95% CI, 0.57–1.00; p = 0.001), and good for tract infiltration (κ = 0.77; 95% CI, 0.53–0.98; p = 0.001). The interobserver agreement was excellent for white matter tract involvement in patients with low-grade gliomas (κ = 0.81; 95% CI, 0.57–1.00; p = 0.001) and high-grade gliomas (κ = 0.91; 95% CI, 0.75–1.00; p = 0.001).Conclusion DTT is a reliable and reproducible method for assessment of white matter tract involvement in patients with low- and high-grade gliomas.
Keywords: glioma; diffusion tensor; tractography